Evaluasi kepatuhan pajak UMKM selama pandemi covid 19 - Marlyna, Diana; Mareta, Ayu Riani; Yufantria, Fenni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The economic downturn during the pandemic affected MSMEs, especially from the number of sales. With declining financial conditions, MSMEs tend to be reluctant to implement tax compliance. From the external element, tax socialization affects tax compliance. This study wants to confirm the effect of MSME financial conditions and tax socialization on tax compliance during the COVID-19 pandemic. The research variables are MSME Financial Condition (X1), Tax Socialization (X2), and Tax Compliance (Y). This research is a quantitative research with hypothesis testing to determine the effect of the independent variable on the dependent variable. Classical test includes normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. All classical tests are met for the variables of MSME financial condition and tax socialization. Hypothesis testing resulted in a significance of less than 0.05, which means the hypothesis is supported, both the first hypothesis and the second hypothesis. It can be concluded that the financial condition of MSMEs has a positive effect on tax compliance and tax socialization also has a positive effect on tax compliance. The limitation of this research is the respondents who are reluctant to fill out the questionnaire. This study provides additional empirical evidence regarding the influence of MSME financial conditions during the pandemic and tax socialization on MSME tax compliance.